Socially responsible investments in financial statements of Polish public companies - Marzena Remlein (European Financial and Accounting Journal, 2018)
Socially responsible investments are one of the most dynamically developing segments of investments and socially responsible investing plays an ever growing role in the world's financial markets. Poland is in the infancy stage of development of socially responsible investments. Socially responsible investing is a decision-making process concerning the allocation of free financial resources, where the investor aims at maximisation of profit and minimisation of risk on one part, and includes the socio-ethical and environmental-ecological considerations on the other. The aim of the paper is to assess the valuation methods and the scope of information on socially responsible investments presented in financial statements of Polish public companies. Assessment of the market of socially responsible investments in Poland according to the European classification of strategies for investing socially responsibly is also purposeful. The paper presents the results of empirical research of valuation and disclosure of SRI in financial statements of Polish public companies.
Keywords: M40; M41; M49; 650; Financial Investments; Investments Property; Respect Index; Socially Responsible Investments; SRI